Investigation of the relationship between technology addiction and sleepiness among university students in health-related departments in Turkey - Citil, Riza; Ufuk Unlu; Yalcin Onder (Journal of the Pakistan Medical Association, 2022)
Abstract Objective: To investigate the relationship of internet and smartphone addiction levels of university students in health-related departments with their daily sleepiness, and to identify associated factors. ---Continue